Pola Pengembangan Aspek Perkembangan Bahasa Anak Usia Dini: Prediksi Trajektori dan Implikasi Pedagogis di Masa Depan - Jamiludin Usman; Sofyan Tsauri; St. Rodliyah; Suhairi Suhairi (Tadris Bahasa Indonesia, Fakultas Tarbiyah, Institut Agama Islam Negeri Madura, 2025)
It is a necessity for educators, parents, and policymakers to understand and optimize the developmental patterns of early childhood language. This research examines the current and future projection of the developmental patterns of early childhood language aspects (receptive, expressive, and literacy). The findings of this study will serve as a practical guide for educators and parents, helping them design appropriate social and personal interventions according to the unique needs of each child. This study uses a descriptive qualitative method with data obtained from document analysis of accreditation results from several early childhood education institutions in East Java. Data analysis was conducted simultaneously using the interactive model approach by Miles, Huberman, and Saldana, which includes data condensation, data display, and conclusion drawing. Data validity was ensured through source and method triangulation. The results show that receptive language is stimulated through activities such as storytelling and expressive language through question-and-answer sessions. Some educators have not yet facilitated children to retell something they know or to express ideas in writing or scribbles. The use of IT to stimulate children's language skills is one of the essential things. It is predicted that there will be a shift towards a more holistic, integrated, and play-based approach, combining all three aspects of language into a complete unit by leveraging IT in the future. In conclusion, language development requires a balance between technological innovation and quality human interaction to optimize a child's linguistic potential.